Enrichment of trace element concentrations in coal and its combustion residues and their potential environmental and human health impact: Can Coal Basin, NW Turkey as a case study. (2016) - Baba, Alper; Gurdal, Gulbin; Yucel, Deniz Sanliyuksel
In this study, the variation of trace element concentrations (total of 48 trace elements including rare earth elements) in coal, coal ash and fly ash were examined and compared with coal Clarke values. Results showed that the average concentrations of trace elements including As, B, Cu, Ce, Co, Cs, Gd, Hf, La, Lu, Mo, Nd, Nb, Pr, Pb, Sc, Sm, Ta, Tb, Th, U, V, W, Y, Yb, Zn and Zr in the Can Basin coals are higher than their respective Clarke values for world low-rank coals. The elements As, Cu, Co, Cs, Mo, Nb, Sc, Pb, Pr, Th, U, V, Zn and Zr are enriched in coal ashes, whereas As, Co, Nb, Sc, U and V are enriched in fly ashes. Among the elements, maximum enrichment in coal was observed for As, with the average concentration of 253.5 ppm As in the Can Basin coals, while the coal Clarke value is 14 ppm and world average value is 8.3 ppm. From the ecotoxicological point of view, combustion residues formed by indoor combustion of coal and/or in thermal power plants may be a hazard to the environment and to aquatic and terrestrial life including human beings, particularly As, trace elements and released radioactive elements.